Effectiveness of outsourcing of security service at Tanzania fisheries research institute, Dar es Salaam - Payowela, Jackson E. (Mzumbe University, 2024)
A dissertation submitted to the School of Public Administration and Managemet in partial fulfillment of the requirements for the award of the degree of Master of Science in Human Resource Management (Msc.HRM) of Mzumbe University